Enhancing auditors' independence in auditing enterprises in Vietnam - Le Doan Minh Duc; Nguyen Thi Hoang Yen; Vo Hoang Ngoc Thuy; Nguyen Hoang Tien; Dinh Ba Hung Anh (Cogent Economics & Finance, 2019)
The working environment of professional auditors can make a threat to independence. There are many studies in the world on this issue but the results are not the same due to differences in each country. By using the qualitative methodology in combination with quantitative data analysis through the period 2016-2017, the study identifies factors affecting auditor independence. The results show that the observed factors that are related to the independent auditor's working environment and that affect the auditor independence are: corporate governance, audit tenure, auditing fee, non-audit service, the auditor-client relationship, and size of audit companies. In particular, the corporate governance of the auditing company has the greatest influence on auditing independence. The paper has contributed to the theoretical body of literature by introducing a theoretical framework for auditors' independence in Vietnam, providing the basis for further research. As a result, the results of the study suggest that auditing firms need to focus on corporate governance that will promote other factors. Moreover, the research contributes to enhancing the auditor independence to meet the expectations of society.
Keywords: 330; Auditor independence; auditing enterprises; Vietnam